Tourism and natural parks en Andalucía after twenty years of their declaration. Statistical analysis, types of parks and current problems - Santos Pavón, Enrique L.; Fernández Tabales, Alfonso (Anales de Geografía de la Universidad Complutense, 2010)
The article presents two main aims. On the one hand, to analyze by means of the objective and measurable existing indicators the evolution of the tourist activity in the andalusian nature parks from their declaration, now twenty years ago.On the other hand, to clarify from statistical information the features that characterize the tourist current situation of the above mentioned parks, showing their principal problems. For all this a classification by types of parks is made and the principle that the tourist utilization of the parks must be based, so much for reasons of sustainability as of competitiveness, in activities narrowly linked to the singularity of their natural capital is defended.
Keywords: Natural parks; Tourism of nature; Sustainable tourism; Tourist indicators; Network of Protected Natural Spaces of Andalusia